Sieve-through vertical flow platform for efficient liquid exchange in particle-based assays - Zhang, Yi (2020)
Particle-based assays are widely used in many biomedical applications. However, the performance of particle-based systems is often compromised by the carry-over contamination caused by the residual reagents during the liquid-exchange process. We have developed a sieve-through platform that utilizes a porous membrane to sieve out the particles, and an absorbent pad to remove the waste liquid by capillary force. The porous membrane is able to contain the liquid in the reaction chamber, and allows the waste liquid to flow through when it is brought into contact with the absorbent pad. The sieve-through platform is able to effectively remove the waste liquid, thereby achieving a more efficient liquid exchange as compared to the conventional process, and minimizing the carry-over contamination. In this study, we have determined the factors that affect the flow characteristics through the porous membrane on the sieve-through platform. We have shown that the sieve-through platform effectively reduces the carry-over contamination. In addition, we have shown particle-based ELISA on the sieve-through platform for the analysis of proteins and cells. We have further demonstrated the potential of the sieve-through platform for high-throughput analysis by presenting a sieve-array, which allows concurrent analysis of multiple samples in parallel. The sieve-through platform can significantly improve the performance of particle-based systems.